COMPARISON OF FERTILITY RESTORATION METHODS IN WOMEN WITH POLYCYSTIC OVARY SYNDROME (Global Conference on Multidisciplinary Research and Innovation, 2026)
Polycystic ovary syndrome (POS) is a leading cause of endocrine infertility. This study evaluates the сomparison of conservative, surgical, and combined treatment methods for POS.
Keywords: infertility, polycystic ovary syndrome, laparoscopy, ovulation stimulation.